Práticas restaurativas pelas polícias judiciárias nos atos infracionais como forma de proteção integral do jovem e fortalecimento da cidadania - Vasconcelos, Rodrigo Ribeiro de (2024)
The aim of this research is to investigate the institutional role of the judicial police, especially the civil police, in view of their residual competence in the face of offenses, and to verify the legitimacy and relevance of the implementation of Restorative Justice by the judicial police in the face of juvenile delinquency, promoting reflection on the paths taken and the strategies to be devised for the comprehensive protection of young people and the strengthening of their citizenship, with a view to social pacification, in order to provoke epistemic indignation in the academic community, legal operators and society in general in the face of this serious issue. This study, produced by the Nucleus of Applied Studies, Law, Childhood and Justice (NUDIJUS) at the Federal University of Ceará, emerges from the social reality in which the state often fails to adequately protect and hold accountable adolescents who infringe the legal system, or, consequently, to effectively curb the development of crime. In the course of this academic work, the relationship between the police and vulnerable populations and between the police and citizenship was investigated, including a study of the genesis and evolution of the civil police in order to gain a better understanding of their powers and how they act in the face of illegal acts. In this vein, the various forms of conflict resolution were analyzed, as well as experiences of applying self-compositional methods of conflict resolution promoted by the judicial police and Restorative Justice projects in the context of criminal acts developed in the state of Ceará, so that, in conjunction with the analysis of the current legal system, it would be possible to formulate answers to the questions raised throughout the chapters. In addition, given the lack of previous references, procedural flows were proposed for the implementation of restorative practices by the judicial police in the sphere of offenses. With the development of the studies, it was concluded that, through the re-signification of police stations and the application of Restorative Justice by the judicial police in cases involving adolescents in conflict with the law, it is possible to promote citizenship and thus enable the integral protection of young people and social pacification. The subject of this study is therefore part of research line 3 of the Postgraduate Program in Law (Stricto Sensu) at the Federal University of Ceará, which is “Social Relations and Legal Thought”, more specifically aligned with the sector “Law and citizenship/indignation and knowledge”, as established in call 001/2023 of the Federal University of Ceará. The research methodology is post-critical and analytical. It also makes use of bibliographic analysis (through books, legal articles and newspapers), documentary analysis (based on national and international documents), legislative analysis (through current and repealed regulations), case law analysis and quantitative and qualitative data gathered specifically on the subject.